Using structural equations to model Akers’ social learning theory with data on intimate partner violence - Cochran, John K. (Crime & delinquency, 2017)
Akers’ social learning theory (SLT) is one of the predominate theories of criminal behavior; moreover, its empirical validity has been consistently supported by the extant research literature. However, a number of limitations plague this literature: Rarely is the full social learning model tested such that all four social learning constructs are operationalized and, where complete tests are found, they have either focused near exclusively on substance use/abuse or have examined only the direct, independent effects of its key theoretical constructs. The present study employs structural equations to test a more complete SLT model against self-reported data on intimate partner violence. Doing so permits an examination of both the direct and indirect effects of differential association, imitation, definitions, and differential reinforcement as well as the reciprocal/feedback effects of intimate partner violence back onto these social learning constructs as explicated by Akers.